A chain kinematic model to assess the movement of lower-limb including wobbling masses. Issue 7 (18th May 2016) - Thouzé, A.; Monnet, T.; Bélaise, C.; Lacouture, P.; Begon, M.
Abstract : Computer simulation models have shown that wobbling mass on the lower limb affects the joint kinetics. Our objective was to propose a non-invasive method to estimate bones and wobbling mass kinematics in the lower limb during hopping. The chain kinematic model has set degrees of freedom at the joints and free wobbling bodies. By comparison to a model without wobbling bodies, the marker residual was reduced by 20% but the joint kinematics remains unchanged. Wobbling bodies' displacements reached 6.9 ± 3.5° and 6.9 ± 2.4 mm relative to the modelled bones. This original method is a first step to assess wobbling mass effect on joint kinetics.